Model for Grade 3 Elementary School Kids' Locomotor Movement Based on Thematic Games - Rafli Rahmat Jacob; Eka Fitri Novitasari; Sujarwo Sujarwo (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. Research has shown that many elementary school teachers lack the understanding and knowledge of the importance of teaching basic locomotor movements beyond the commonly known walking, running, and jumping. Basic locomotor movements encompass a wider range of movements such as hopping, galloping, and more. To address this, Basic Locomotor Movement Models Based on Thematic Games for Class Children 3 Elementary Schools aims to develop basic motion models that are tailored to children's growth, development, and characteristics. These models are designed to be implemented through physical activities that focus on teaching basic locomotor movements. Materials and methods. This study employs the thematic game-based ADDIE approach for teaching movement education to grade 3 elementary school children. The purpose of this model is to enhance the learning process and help students comprehend various kinds of physical movements in daily life. The study follows a development model consisting of five steps: analysis, design, development, implementation, and evaluation. Results. The study results have been presented in the form of a book that contains basic motion models that are tailor-made for third-grade students in elementary school. The book aims to provide a comprehensive understanding of fundamental motion concepts in a simplified manner that is easy for kids to comprehend. Conclusion. Based on the conducted research, the model developed is deemed highly appropriate for the characteristics and curriculum material of grade 3 elementary school children. The model is considered suitable for the effective implementation of basic movement learning.